Investigation into the event-activity dependence of gamma(nS) relative production in proton-proton collisions at root s=7 TeV - (:unkn) unknown (SPRINGER, 2020)
The ratios of the production cross sections between the excited gamma(2S) and gamma(3S) mesons and the gamma(1S) ground state, detected via their decay into two muons, are studied as a function of the number of charged particles in the event. The data are from proton-proton collisions at root s = 7TeV, corresponding to an integrated luminosity of 4.8 fb(-1), collected with the CMS detector at the LHC. Evidence of a decrease in these ratios as a function of the particle multiplicity is observed, more pronounced at low transverse momentum p(T)(mu mu). For gamma(nS) mesons with p(T)(mu mu) > 7 GeV, where most of the data were collected, the correlation with multiplicity is studied as a function of the underlying event transverse sphericity and the number of particles in a cone around the gamma(nS) direction. The ratios are found to be multiplicity independent for jet-like events. The mean p(T)(mu mu) values for the gamma(nS) states as a function of particle multiplicity are also measured and found to grow more steeply as their mass increases.
Keywords: B physics; Hadron-Hadron scattering (experiments); Particle correlations and fluctuations; Quarkonium; PP COLLISIONS; PARTICLE MULTIPLICITY; PBPB COLLISIONS; CROSS-SECTIONS; COLLECTIVITY; UPSILON(2S); STATE; LHC